2000
DOI: 10.1097/00002060-200009000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Passive Motion After Total Knee Arthroplasty

Abstract: Although power analysis indicated the need for differences in results for 32 patients per group to achieve significance, the difference between the two groups suggested neither statistical nor clinical significance. We concluded that the use of CPM in the rehabilitation hospital is likely of no added benefit to patients admitted after single total-knee replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…The findings of this study have indicated that CPM use for 1 hour twice a day following TKA has no influence on flexion, extension or pain which is in agreement with Beaupre et al [10], Chen et al [13], Montgomery and Eliasson [11] and Ritter et al [14]. Interestingly mean range of flexion outcome at final follow-up was greater than the preoperative range in both groups (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of this study have indicated that CPM use for 1 hour twice a day following TKA has no influence on flexion, extension or pain which is in agreement with Beaupre et al [10], Chen et al [13], Montgomery and Eliasson [11] and Ritter et al [14]. Interestingly mean range of flexion outcome at final follow-up was greater than the preoperative range in both groups (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…This is unsurprising, and is not comparable with current practice as patients are usually permitted to mobilise or commence flexion immediately postop. Under these circumstances no difference in range of flexion are found [8][9][10][11][12][13][14] with any quicker attainment of flexion [15][16][17] insignificant at longer term follow-up [7,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies 1,3,4,6,10,[12][13][14]16 were identified that compared standardised PT plus CPM with a control group that received only the standardised rehabilitation programme. Two studies 13,16 did not report a short-term measurement, so these were not included in the metaanalysis of short-term effects.…”
Section: Cpm + Pt Versus Ptmentioning
confidence: 99%
“…Some trials have shown positive effects on early postoperative knee ROM, [1][2][3][4][5][6]8 whereas other studies have found no difference in ROM. [9][10][11][12][13][14][15][16] Nearly all authors concluded that the use of CPM did not result in better ROM 3-6 months after the operation. This review focuses on flexion ROM because gain of flexion ROM is the prime reason for adding CPM in a rehabilitation programme following TKA.…”
mentioning
confidence: 99%
“…One study reported that the pain experienced during rehabilitation after TKA was one of the main issues of concern for patients before TKA [26]. While PROME using a CPM device has been the subject of many studies [7,9,17,20,22,23,27,30,33,35,36], to the best of our knowledge, there have been no reports on the clinical value of PROME by a physical therapist after TKA. This study examined whether or not the incorporation of regular PROME by a physical therapist would offer additional clinical benefits to the knees with TKA in terms of the pain experienced during physiotherapy, the ROM and the scores of the American Knee Society (AKS) and Western Ontario McMaster University Osteoarthritis Index scales (WOMAC).…”
Section: Introductionmentioning
confidence: 99%